Management of Bilateral Malignant Ovarian Germ Cell Tumors. Issue 2 (February 2015) - Sigismondi, Cristina; Scollo, Paolo; Ferrandina, Gabriella; Candiani, Massimo; Angioli, Roberto; Viganò, Riccardo; Scarfone, Giovanna; Mangili, Giorgia
<x xml:space="preserve">Abstract</x> Objectives Bilaterality is rare in malignant ovarian germ cell tumors (MOGTs). The bilateral ovarian involvement represents a critical issue when diagnosed in young women desiring to preserve fertility. The aim of this study was to evaluate clinical characteristic and management of patients bilateral MOGTs. Methods Patients affected by bilateral MOGT and treated at MITO group centers were reviewed. Results In 145 patients with MOGTs, 5.5% were bilateral. Three patients were affected by dysgerminoma (associated with bilateral gonadoblastoma in 1), 2 by immature teratoma, 2 by mixed germ cell tumors, and 1 by embryonal carcinoma. International Federation of Gynecology and Obstetrics stage was 3 IB, 1 IC, 3 IIIC, and 1 IV. Three patients received radical surgery, and the patient with dysgerminoma associated with gonadoblastoma received bilateral adnexectomy. Four patients received fertility-sparing surgery; 2 patients received unilateral salpingo-oophorectomy and contralateral cystectomy; in 2 patients, the ovaries were completely transformed in neoplastic tissue; suspecting a contralateral dysgerminoma histology, a unilateral salpingo-oophorectomy and contralateral biopsy were performed, and the contralateral neoplastic ovary was left unresected. Six patients received adjuvant chemotherapy. Seven patients are disease free after a median follow-up of 54 months. The patient affected by embryonal carcinoma died of disease. Two patients resumed menstruation, and one had a pregnancy. A compromised ovarian function was found in 2 patients, and they were addressed to oocyte cryopreservation. Conclusions Bilateral MOGTs have a good prognosis. In dysgerminoma histology, residual disease could be left to spare fertility. An oncological and reproductive function follow-up is recommended.